The first cytogenetic report of fireflies (Coleoptera, Lampyridae) from Brazilian fauna - Dias, Carolina M.; Schneider, Marielle C.; Rosa, Simone P.; Costa, Cleide; Cella, Doralice M. (Blackwell Publishing, 2007)
The first cytogenetic analysis of fireflies from Brazilian fauna was carried out in this work. The investigation of two species of the subfamily Lampyrinae, Aspisoma maculatum and Photinus sp. (aff. pyralis), showed the diploid number 2n = 19 and an X0 sex determination system in males. These observations are similar to those already described for all the Lampyrinae species previously studied. In contrast, Bicellonycha lividipennis (Photurinae) revealed the karyotype 2n = 16 + neoXY, which has not yet been registered for any firefly species. The neoXY sex determination system encountered in this species probably arose through fusion between an ancestral X sex chromosome, belonging to the X0 system, and an autosomal element. This event also reduced the diploid number from 2n = 19, which is more frequent in the family Lampyridae, to 2n = 18 in B. lividipennis. The analysis of meiotic cells showed that the neoXY sexual bivalent of B. lividipennis exhibited a prominent terminal chiasma, indicating that the sex chromosomes are not wholly differentiated and still retain a region of homology. A review of the cytogenetic data known for the family Lampyridae was also documented in this work, as well as a discussion on the main trends of chromosomal evolution that seem to have occurred in this group.
Keywords: Aspisoma maculatum; Bicellonycha lividipennis; chromosome; meiosis; Photinus sp